Language clinic effects in cases of subjects with cerebral palsy - Vasconcellos, Roseli [UNESP] (Univ Federal Minas Gerais, Fac Letras, 2018)
This article stems from the thesis Organism and subject: a sensitive difference in cerebral palsies (VASCONCELLOS, 2010) theoretically based on the Brazilian Interactionism (DE LEMOS, 1992, 2002, 2006, 2007 among others) and its consequences for the Acquisition, Pathologies and Language Clinic Integrated Project coordinated by Maria Francisca Lier-DeVitto and Lucia Arantes (LAEL/PUC-SP). Both in the thesis and in this article the aim was to deepen a discussion that pointed out to pulsional body effects, despite obstacles concerning the subjects with cerebral palsy organic condition who do not speak, aiming to demonstrate the viability of a Language Clinic therapy conducted without a focused reasoning on these subjects' motor difficulties. Medicine was approached from a dialogue with Neurology, aiming to establish its distinction of the pulsional body, focusing on the newest findings (neuroimaging techniques) and their relations with the oldest (Freud's claims about the nature of cerebral palsy) which suggest strong convergence. The difference, both theoretical and clinical introduced in the thesis for the treatment of such subjects, is highlighted by these clinic effects including Augmentative and Alternative Communication and their graphic-visual symbols systems that enable the materialization of the significant, which is done by way of loaning the therapist's body and voice. Patient data analyzed were collected in dialogic clinical situations, referred to the presence of a body-language and to the heterogeneities in their effects promoted in this clinic, which raised considerations about the pleasure accompanying certain vocalized speech productions in two cases and conflict, in another one.
Keywords: cerebral palsy; language; speech language and hearing sciences; language clinic; augmentative and alternative communication